Yoga and Physical Education: Its Impact on Wellbeing - K.V.S. NAIDU; M. VASUDEVA RAJU (International Journal on Integrated Education, 2022)
Yoga is a philosophical system from India that emphasises the importance of working with the body to develop healthy behaviours and thoughts. Physical postures, known as asanas in Sanskrit, are among the techniques learned. Athletics and gymnastics are part of the Physical Education programme, as you may recall. There was a time when people said, "It's not the winning itself that matters, but the nobly competing," when the location of competitions was sacred and respect between competitors was essential. Yoga can help athletes improve their mind control and concentration, which will help them perform better on the field. It provides children and adults with the opportunity to achieve success in physical activity, which can help build a strong foundation for life. Yoga and physical education both use the body as a resource for improving behaviours and skills that are essential for maintaining physical and mental well-being. They are now considered complementary topics. Whereas the West established physical exercise and athletic training and focused on its positive health partnership, the East used meditation and relaxation to achieve the same goals.